PENGARUH MEDIA PEMBELAJARAN RODA PINTAR TERHADAP KEMAMPUAN BERHITUNG PADA SISWA KELAS RENDAH SD INPRES MOROWA - Ramadhani, Naimatul; Fatimah, Waddi; Damayanti, A. Alfiani; Fitriana HS, Eka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Articles in the Jurnal Pendidikan dan Pembelajaran Indonesian (JPPI) are written This study aims to determine the effect of using the "Roda Pintar" (Smart Wheel) media on the arithmetic abilities of lower-grade students at SD Inpres Morowa. This research is an experimental study using a quantitative approach. The population in this study consists of all second-grade students. The sampling technique used in this study is purposive sampling. The sample consisted of 37 second-grade students, including 22 boys and 15 girls.The data collection method was analyzed using SPSS for Windows. The results of the descriptive statistical analysis showed an average teacher activity score of 3.7 and an average student activity score of 3, both categorized as good. Inferential analysis showed that the normality test for pretest and posttest results had a significance value of 0.179 (greater than 0.05), indicating that the data were normally distributed. The homogeneity test showed a significance value of 0.97, indicating that the data were homogeneous. Furthermore, the hypothesis test showed a significance value of 0.000 (less than 0.05), meaning that the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected.Based on the results of the research conducted, it can be concluded that the use of the "Roda Pintar" media has a significant effect on the arithmetic abilities of lower-grade students at SD Inpres Morowa.